2013
DOI: 10.1063/1.4815965
|View full text |Cite
|
Sign up to set email alerts
|

Strain localization in a nanocrystalline metal: Atomic mechanisms and the effect of testing conditions

Abstract: Abstract:Molecular dynamics simulations are used to investigate strain localization in a model nanocrystalline metal. The atomic mechanisms of such catastrophic failure are first studied for two grain sizes of interest. Detailed analysis shows that the formation of a strain path across the sample width is crucial, and can be achieved entirely through grain boundary deformation or through a combination of grain boundary sliding and grain boundary dislocation emission.Pronounced mechanically-induced grain growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 66 publications
5
28
0
Order By: Relevance
“…The possibility of purely grain-boundary-mediated deformation has been reported before for Ni [67], where it is enabled by a free percolation path for shear bands through the sample. Our results furthermore indicate that the participation of the crystalline phase in the deformation also depends on the intrinsic proclivity towards strain localisation in the amorphous phase.…”
Section: Change Of Mechanisms As a Jamming Transitionmentioning
confidence: 60%
“…The possibility of purely grain-boundary-mediated deformation has been reported before for Ni [67], where it is enabled by a free percolation path for shear bands through the sample. Our results furthermore indicate that the participation of the crystalline phase in the deformation also depends on the intrinsic proclivity towards strain localisation in the amorphous phase.…”
Section: Change Of Mechanisms As a Jamming Transitionmentioning
confidence: 60%
“…(13.1.3) predicts enormous strengthening as the grain size is reduced to the atomic scale (and the microstructure becomes amorphous); in practice, once the grain size goes below ∼10 nm, plasticity becomes controlled by other mechanisms (primarily grain boundary sliding [53] and shear banding [54]). Eq.…”
Section: Scale-dependent Yield Strength In Metalsmentioning
confidence: 99%
“…It is also found that the transition in plastic deformation mechanisms in metals strongly depends on temperature. For example, Hughes and Hansen [9] have revealed that at low temperatures, the dislocation-based plasticity in nanostructured metals may exist far below the transition suggested by previous experiments and molecular dynamics (MD) simulations, with a limit of <5 nm.On the other hand, one-dimensional metal nanostructures such as nanowires (NWs) and nanopillars have attracted significant attention in recent years due to their unique mechanical properties [10][11][12][13][14][15][16][17]. As compared to bulk nanocrystalline metals, the plasticity in metal NWs and nanopillars is more complicated due to the possible contribution from the external free surfaces [14].…”
mentioning
confidence: 99%
“…On the other hand, one-dimensional metal nanostructures such as nanowires (NWs) and nanopillars have attracted significant attention in recent years due to their unique mechanical properties [10][11][12][13][14][15][16][17]. As compared to bulk nanocrystalline metals, the plasticity in metal NWs and nanopillars is more complicated due to the possible contribution from the external free surfaces [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation